Effect of the Alloying Metal on the Corrosion Resistance of Pd-Rich Binary Alloys with Pt, Rh, and Ru in Sulfuric Acid - Katarzyna Hubkowska (Materials, 2021)
The paper presents the study of the corrosion resistance of electrodeposited Pd and its binary alloys with Pt, Rh, and Ru on a polycrystalline Au substrate. The corrosion resistance was tested in 0.5 M sulfuric acid at room temperature using potentiodynamic polarization and electrochemical impedance spectroscopy techniques. The morphology/composition and work function values were determined by scanning electron microscopy/energy–dispersive X–ray spectroscopy and scanning Kelvin probe, respectively. The obtained results revealed that the Pd electrode is the most resistant to corrosion, whereas the Pd-Ru electrode is the most susceptible to dissolution. It was found that the corrosion resistance of Pd-binary alloys decrease in the following order: Pd > Pd-Pt > Pd-Rh > Pd-Ru. This effect was assigned mainly to the difference in surface roughness factor of tested electrodes.